2020
DOI: 10.3389/fpsyg.2020.00376
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Framework for the Analysis of Program Notes Written for Contemporary Classical Music Concerts

Abstract: At classical music concerts, a program note is the usual medium for communicating information about the music to be heard and performed. Although there may be crossover of information, the program note is distinct from the CD cover note, from notes contained within a musical score note, and from a composer's directions for performers. With a focus on contemporary classical works in the Australian context, the researchers' aim in this study was to develop and test an analytical frame of informational categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…As an aspect of the Research Methods and Thesis Writing class at graduate student level, student performers are expected to write program notes about their performance for a general concert audience, that is, an audience of non-musicians who are interested in music and fairly knowledgeable. The goal of teaching program notes is to increase the audience's understanding and enjoyment of the music performed (Blom et al, 2020).…”
Section: Schumann's Piano Piece Papillons Op 2 Program Notes For a Cl...mentioning
confidence: 99%
“…As an aspect of the Research Methods and Thesis Writing class at graduate student level, student performers are expected to write program notes about their performance for a general concert audience, that is, an audience of non-musicians who are interested in music and fairly knowledgeable. The goal of teaching program notes is to increase the audience's understanding and enjoyment of the music performed (Blom et al, 2020).…”
Section: Schumann's Piano Piece Papillons Op 2 Program Notes For a Cl...mentioning
confidence: 99%
“…At classical music concerts, a program note is the usual medium for communicating information about the music to be heard and performed. Although there may be information in common, the program note is distinct from the CD cover note, from notes contained within a musical score, and from a composer's directions to performers (Blom et al, 2020). German romantic composer and pianist, Robert Schumann (1810-1856) demanded program notes (Koller, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Concert programmes are a long-established part of Western concert and orchestral life, yet scholars have commonly argued that academic research into them is sparse (Bashford, 2019;Blom, Bennett & Stevenson, 2020;Ridgewell, 2010;Tewinkel, 2016). In the available literature, one aspect, however, continues to stand out.…”
Section: Programme Notes or Concert Programmes?mentioning
confidence: 99%
“…Various scholars locate programme notes' main purpose in guiding concertgoers through the musical work in order to enhance their experience and enjoyment by increasing the understanding of the music (Harries, 2017;Ridgewell, 2003;Scaife, 2001;Thorau, 2020;Wingell, 2009). The authors further pinpoint three main types of information that can be found in programme notes: (1) contextual information on the background of a work, such as the context of its creation or the personal life of a composer; (2) descriptive and metaphorical information that describe the feeling or mood of a musical work; and (3) analytical information, such as on the structure or instrumentation of a piece (Blom, Bennett, & Stevenson, 2020, section 'Program note content'). 28 Both the key functions as well as the kinds of information incorporated by the notes are the result of nineteenth-century aesthetic ideals, such as the intellectual engagement with music as a primary means to appreciate and experience it.…”
Section: Programme Notes: Content Reception and Writing Stylesmentioning
confidence: 99%
See 1 more Smart Citation